2020
DOI: 10.3892/ol.2020.12109
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine resistance in triple‑negative breast cancer cells can be reverted by <em>Drosophila melanogaster</em> deoxyribonucleoside kinase in the nucleus or cytosol

Abstract: The development of drug resistance to chemotherapeutic agents has consistently presented a challenge in terms of the treatment of patients with triple-negative breast cancer (TNBC). In the present study, gemcitabine (dFdC)-resistant TNBC cells were established, and the effects of lentivirus-deoxyribonucleoside kinase (dNK) and a mutated form of dNK (lentivirus-dNKmut) on reversing the acquired drug resistance in dFdC-resistant TNBC cells were explored. Quantitative PCR and western blotting experiment results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The VEGF promoter was obtained from 4T1 cell lines and inserted into the pEGFP-N1 expression plasmid. Another plasmid was constructed under the control of the CMV promoter, as a standard promoter [51], to make an appropriate comparison between the function of the VEGF promoter and the standard CMV promoter. The results of bystander effect test and real-time PCR showed that the VEGF promoter function can act close to the CMV promoter of the standard pEGFP-N1 plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF promoter was obtained from 4T1 cell lines and inserted into the pEGFP-N1 expression plasmid. Another plasmid was constructed under the control of the CMV promoter, as a standard promoter [51], to make an appropriate comparison between the function of the VEGF promoter and the standard CMV promoter. The results of bystander effect test and real-time PCR showed that the VEGF promoter function can act close to the CMV promoter of the standard pEGFP-N1 plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the drug resistance induced by nucleoside kinase deficiency, various therapeutic approaches have been postulated. In this context, a multisubstrate deoxyribonucleoside kinase of Drosophila melanogaster in the nucleus or cytosol has been reported as a potential candidate suicide gene for reversing acquired dFdC resistance in TNBC cells [30].…”
Section: Conventional Chemotherapymentioning
confidence: 99%
“…Gemcitabine, a pyrimidine nucleoside analog anticancer drug, is effective in most solid tumors, and cisplatin combined with gemcitabine is the preferred chemotherapy strategy in patients with metastatic TNBC (Hu et al., 2015; Miao et al., 2020; Poggio et al., 2018). Although gemcitabine is clinically effective, chemoresistance remains a barrier to cancer treatment (Zhao et al., 2020). Factors affecting gemcitabine resistance were previously explored.…”
Section: Introductionmentioning
confidence: 99%